2021
DOI: 10.1039/d0nr04019c
|View full text |Cite
|
Sign up to set email alerts
|

One-step construction of ferritin encapsulation drugs for cancer chemotherapy

Abstract: A simple preparation of high drug-loaded ferritin nanomedicines was demonstrated. By mixing ferritin and a drug, an electrostatic potential with a small ferritin cavity facilitated the passage and the deposition of the drug in the cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 49 publications
0
36
0
1
Order By: Relevance
“…HFn decomposes into its subunits in an acidic pH environment and reassembles after returning to a neutral pH, which is one of the most commonly used drug loading methods (Kim et al., 2011 ). However, recent studies have found that treatment with acidic pH will irreversibly destroy HFn and form holes on the surface of the nanocage (Inoue et al., 2021 ). Therefore, we chose mild urea treatment, reassembled after gradual removal of urea, and encapsulated the Cur molecules in HFn nanocages.…”
Section: Resultsmentioning
confidence: 99%
“…HFn decomposes into its subunits in an acidic pH environment and reassembles after returning to a neutral pH, which is one of the most commonly used drug loading methods (Kim et al., 2011 ). However, recent studies have found that treatment with acidic pH will irreversibly destroy HFn and form holes on the surface of the nanocage (Inoue et al., 2021 ). Therefore, we chose mild urea treatment, reassembled after gradual removal of urea, and encapsulated the Cur molecules in HFn nanocages.…”
Section: Resultsmentioning
confidence: 99%
“…Such as methods that target TFR1, which is commonly overexpressed in tumor cell species. W. Liu et al developed endogenous human ferritin heavy-chain nanocages (HFn) to serve as the carrier of paclitaxel (PTX), which can specifically bind to blood-brain barrier and TFR1 widely overexpressed in glioma cells, and showed that HFn-PTX showed the best antitumor effect, and the median survival time was significantly longer than that of free PTX (207); additionally, doxorubicinloaded ferritin heavy chain (DOX-FTH) can be taken up and induce apoptosis of cancer cells overexpressing TFR1 (208); and Cheng et al indicated that HFn-Dox treatment could significantly improve the therapeutic effect of doxorubicin on gastric cancer, and increase overall survival rate of tumorbearing mice (179).…”
Section: Ferroptosis Inducersmentioning
confidence: 99%
“…In addition to DOX, this new method successfully introduced more than a dozen drug molecules (metformin, nicotinamide, creatinine, famotidine, rhodamine B, etc.) into the ferritin nanocage [73]. The development of new drug loading methods is expected to promote the clinical transformation of ferritin nano-drug delivery systems.…”
Section: Ferritin Nanoparticles Combined With Photothermal Therapy (Ptt)mentioning
confidence: 99%